Sosioantropologi penyakit antraks di Indonesia: Kajian Literatur Review - Sutaip, Sutaip; Maulana, Moh. Hafidz Affan; Finani, Moh. Zaenal; Abshor, M. Caesar Ulil; Setiawan, Gilang (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Anthrax is a disease that is spread globally and is endemic in several countries, including Indonesia. Outbreaks of disease that attack animals in a specific area are usually influenced by ecological, demographic, and sociocultural aspects. Purpose: To determine knowledge, attitudes, and behavior towards anthrax in socio-anthropological studies. Method: Systematic literature research compiled based on the Preferred Reporting Items For Systematic Review and Meta Analysis (PRISMA) guidelines. The literature review used three databases -pubmed, sciencedirect, and google scholar, resulting in 10 articles being evaluated. Results: The 10 evaluated journals revealed that 60% (6/10) of the studies stated that the low level of public knowledge about anthrax disease including symptoms, transmission, and prevention. In addition, 50% (5/10) of the literature stated that the public's habit of consuming meat from livestock that died suddenly increased the risk of anthrax transmission. This negative attitude is also reflected in the public's preference to get vaccines from shamans rather than official health services. The knowledge gap is a major factor driving this risky behavior. Conclusion: The occurrence of anthrax disease is related to the knowledge, behavior, and attitudes of society in socio-anthropological studies, so that more effective education and socialization are needed to increase public understanding and awareness.   Keywords: Anthrax; Attitude; Behavior; Control; Farmers; Indonesia; Knowledge; One Health; Prevention; Zoonosis.   Pendahuluan: Antraks adalah penyakit yang tersebar secara global dan menjadi endemik di beberapa negara, termasuk Indonesia. Wabah penyakit yang menyerang hewan di suatu wilayah yang spesifik biasanya dipengaruhi oleh aspek ekologis, demografis, dan sosiokultural. Tujuan: Untuk mengetahui pengetahuan, sikap, dan perilaku terhadap antraks dalam kajian sosioantropologi. Metode: Penelitian literatur sistematis yang disusun berdasarkan pedoman Preferred Reporting Items For Systematic Review and Meta Analysis(PRISMA). Ulasan literatur menggunakan tiga database-pubmed, sciencedirect, dan google scholar, sehingga diperoleh 10 artikel yang dievaluasi. Hasil: 10 jurnal yang dievaluasi mengungkapkan bahwa 60% (6/10) penelitian menyatakan bahwa rendahnya tingkat pengetahuan masyarakat tentang penyakit antraks termasuk gejala, penularan, dan pencegahan. Selain itu, 50% (5/10) literatur menyatakan kebiasaan masyarakat mengonsumsi daging hewan ternak yang mati secara mendadak sehingga meningkatkan risiko penularan antraks. Sikap negatif ini juga tercermin dari preferensi masyarakat untuk mendapatkan vaksin dari dukun daripada layanan kesehatan resmi. Kesenjangan pengetahuan menjadi faktor utama yang mendorong perilaku berisiko ini. Simpulan: Kejadian penyakit antraks berkaitan dengan pengetahuan, perilaku, dan sikap masyarakat dalam kajian sosioantropologi, sehingga perlunya edukasi dan sosialisasi yang lebih efektif untuk meningkatkan pemahaman dan kesadaran masyarakat.   Kata Kunci: Antraks; Indonesia; One Health, Pencegahan, Pengendalian; Pengetahuan; Perilaku; Peternak; Sikap; Zoonosis.